A escuta profética e não profética na alteridade: uma reflexão a partir da ética de Lévinas - Costella, Silvério (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
This reflection addresses two ways of welcoming the other in suffering, through a prophetic and non-prophetic nature. On the one hand, it refers to listening to the other, aiming at the interests of the self, with an omnipotent attitude, autonomy of conscience andabsence of sensitivity. It is associated with the alienating theological discourse, articulated by false prophets. The other tendency welcomes the other in their misery, assuming responsibility for them, being the condition for subjective identity, in a relationship of heteronomy, associated with the discourse of the true prophet. These modes of hospitality represent two treacherous poles to each other, due to the proximity of brotherhood between good and evil, the good and the bad prophet.
Keywords: Listen; good; bad; prophet